U.S. Supreme Court Precedents on Arbitration : Shaping the American Arbitration Law and Practice - Advogados, Cesar Asfor Rocha; Carmona, Carlos Alberto; Duggal, Kabir; Lahlou, Yasmine; Lindsey, Chaffetz; Vaughn, Gustavo Favero (International Law E-Books Online, Collection 2025., 2025)
For every lawyer practicing or aspiring to practice law in the US and every student striving to become a well-rounded litigator, familiarity with relevant case law is indispensable. This axiom holds particularly true in the realm of arbitration. As the ultimate arbiter on arbitration matters in the US, the decisions of the US Supreme Court carry paramount significance. This book serves as a vital resource, offering detailed analysis of nearly 40 cases by arbitration experts well-versed in the intricacies of the US legal system. Through meticulous commentary and critique, it vividly illustrates how SCOTUS has profoundly influenced the landscape of arbitration law and practice over the years.